2016
DOI: 10.1101/095042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the Heat Dissipation from Molecular Motor’s Transport Properties in Nonequilibrium Steady States

Abstract: Theoretical analysis, which maps single molecule time trajectories of a molecular motor onto unicyclic Markov processes, allows us to evaluate the heat dissipated from the motor and to elucidate its dependence on the mean velocity and diffusivity. Unlike passive Brownian particles in equilibrium, the velocity and diffusion constant of molecular motors are closely inter-related to each other. In particular, our study makes it clear that the increase of diffusivity with the heat production is a natural outcome o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…11,19,[34][35][36][37][38] Unlike in our model, all other models we have found assume that rate constants only explicitly contain splitting factors for force, with no splitting factors for other free energy components (though one other model has implicit splitting of the effect of chemical potential 11 ). Splitting factor analysis has largely been done in the context of 'canonical' molecular machines, such as the walking motors kinesin, [35][36][37][38] myosin, 11,19 and dynein, 39 or the rotary motor F1-ATPase. 34 Splitting factors δ are not always robust, with distinct data sets for kinesin motility 40,41 leading to substantially different inferred values of 0.3 and 0.65.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…11,19,[34][35][36][37][38] Unlike in our model, all other models we have found assume that rate constants only explicitly contain splitting factors for force, with no splitting factors for other free energy components (though one other model has implicit splitting of the effect of chemical potential 11 ). Splitting factor analysis has largely been done in the context of 'canonical' molecular machines, such as the walking motors kinesin, [35][36][37][38] myosin, 11,19 and dynein, 39 or the rotary motor F1-ATPase. 34 Splitting factors δ are not always robust, with distinct data sets for kinesin motility 40,41 leading to substantially different inferred values of 0.3 and 0.65.…”
Section: Discussionmentioning
confidence: 95%
“…We have shown that both low and high splitting factors can maximize flux, and that the optimal splitting factor value depends on the allocation of free energy. Experimental fits of splitting factors find both low splitting factors 11,19,[34][35][36] and high splitting factors. 35,37 These fits use several models for the dependence of rate constants on resisting forces.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…305 Recent work has argued that enzyme diffusion enhancement due to catalysis fits within the same framework that describes the diffusion enhancement of traditional motors, such as kinesin, due to dissipation. 176…”
Section: Enzyme Diffusion Enhancementmentioning
confidence: 99%
“…The binding and hydrolysis of ATP are the events associated with the NL docking (19). Based on these observations and other key experiments probing the variations of the stepping characteristics of the motor as a function of ATP concentration and applied load, several theoretical models for motors in general and the the catalytic cycle of Kin1 in particular have been proposed (15,(20)(21)(22)(23)(24)(25), although issues such as the mechanism of inter-head communication (gating) continue to be topics of interest (26)(27)(28).…”
mentioning
confidence: 99%